Wage differences between women and men in Sweden: The impact of skill mismatch - Mats Johansson; Katarina Katz (Institute for Labour Market Policy Evaluation (IFAU), 2006)
We investigate skill mismatch and its impact on gender differences in wage gap and in returns to education in Sweden 1993 to 2002.Women are more likely to have more formal education than what is normally required for their occupation (overeducation), while men are more likely to have less (undereducation).Over- and undereducation contribute far more to the gender wage gap than years of schooling and work experience. In decompositions, adjusting for skill mismatch decreases the gender wage gap by between one tenth and one sixth. This is roughly a third to a half as much as is accounted for by segregation by industry. Thus, taking skill mismatch into account is essential for the analysis of gender wage differentiation, even though it does not alter the result that the estimated returns to education are smaller for women than for men in Sweden.
Keywords: J16; J24; J31; J71; 330; Gender differentials; discrimination; over- and undereducation; Lohndifferenzierung; Bildungsertrag; Matching; Geschlecht; Fraueneinkommen; Schweden